Operacja zaćmy z wszczepieniem sztucznej soczewki wewnątrzgałkowej u dzieci z przewlekłym zapaleniem błony naczyniowej - Urban, Beata; Bakunowicz-Łazarczyk, Alina (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: To evaluate the visual outcome of cataract surgery with intraocular lens (IOL) implantation in children with chronic uveitis. Material and methods: The records of seven children (9 eyes), with chronic uveitis who had cataract extraction with IOL implantation between 2001 and 2007, were retrospectively examined. The mean follow-up was 47.9 months, respectively. The postoperative visual outcome and complications were analyzed. Results: The mean age of 2 girls and 5 boys was 17.4 years (range from 12 to 21 years). 5 patients had unilateral cataract. 6 patients underwent cataract extraction with IOL implantation, one patient underwent combined cataract surgery with IOL implantation and trabeculectomy. Median age at surgery was 17.7 years. At the final follow-up examination 8 eyes (88.9%), had improved visual acuity. The visual acuity was 20/20 in one eye, 20/40 or better in 5 eyes and 20/50 in 3 eyes. Posterior capsule opacification was observed in 5 eyes, high intraocular pressure in 2 eyes and cystoid macular edema in 1 eye. Conclusions: The outcomes of cataract extraction with IOL implantation in children’s eyes with chronic uveitis may be satisfactory. Correct time of surgery, adequate long-term preoperative and postoperative anti-inflammatory therapy may promote good results.